Efeito do sombreamento e do substrato sobre a germinação e o crescimento de plântulas de Acacia mangium E Acacia mearnsii - Martins, Cibele Chalita [UNESP]; da Silva, José Diego Rodrigues; Pereira, Maria Renata Rocha [UNESP]; de Oliveira, Silvia Sanielle Costa [UNESP] (My University, 2012)
The speed and uniform germination of seeds, followed by the prompt seedling emergence, are highly desirable characteristics in seedling production. Studies aiming to enable the use of organic waste such as sewage sludge and pine bark in the supply chain represent a current demand. The aim of this study was to identify conditions of shading and substrate which are more favorable to the process of seed germination and seedling growth of Acacia mangium and Acacia mearnsii. After overcoming dormancy in hot water, the seeds were sown in three substrates: substrate plantmax commercial forest (control), pine bark and pine bark mixed with biosolids (1:1). The tubes were placed in a tree nursery under three shading conditions: 50%, 30% and 0% (full sun). The evaluated parameters were: speed and germination percentage (daily until 30 days) and shoot length of seedlings (weekly from 75 to 150 days). The experiment was a completely randomized design with treatments in a factorial 3 x 3 and the results were submitted to regression analysis. The highest germination was obtained in the sowing of Acacia mangium in pine bark at 30% shading and commercial substrate at 30 and 50% shading for Acacia mearnsii in pine bark under 50% shading or commercial substrate in full sun. For both species, seedlings grew faster and reached larger size in the final substrate of pine bark with biosolids and in any condition of shading (30 e 50 %) and full sun, anticipating the production of seedlings.
Effect of shading and substrate on the germination and seedling growth of Acacia mangium and Acacia mearnsii
Keywords: Forest species; Pine bark; Seeds; Sewage sludge